Sistem Pendukung Keputusan Penentuan Guru Bidang Studi Pada Sekolah SMK Siti Banun Rantauprapat Menggunakan Metode Simple Additive Weighting (SAW) - Hsb, Heri Faysal; Ritonga, Wahyu Azhar; Subagio, S (U-NET Jurnal Teknik Informatika, 2024)
Teachers are one of the most important components owned by schools in sustaining life, which is a challenge for the management of educational institutions to be able to provide an appropriate, effective and efficient decision in managing data in an increasingly competitive business world that encourages schools to work harder. in improving the quality of their schools. The Decision Support System or SPK for determining subject teachers with the (SAW) method produces a system that can determine an option that can assist the head in making decisions. The simple additive weighting (SAW) method applies a weighted average to calculate the amount of production as the final result.